Modulation of GPR133 (ADGRD1) signaling by its intracellular interaction partner extended synaptotagmin 1 - Gabriele Stephan; Sara Haddock; Shuai Wang; Hediye Erdjument-Bromage; Wenke Liu; Niklas Ravn-Boess; Joshua D. Frenster; Devin Bready; Julia Cai; Rebecca Ronnen; Jonathan Sabio-Ortiz; David Fenyo; et al. (Cell Reports, 2024)
Summary: GPR133 (ADGRD1) is an adhesion G-protein-coupled receptor that signals through Gαs/cyclic AMP (cAMP) and is required for the growth of glioblastoma (GBM), an aggressive brain malignancy. The regulation of GPR133 signaling is incompletely understood. Here, we use proximity biotinylation proteomics to identify ESYT1, a Ca2+-dependent mediator of endoplasmic reticulum-plasma membrane bridge formation, as an intracellular interactor of GPR133. ESYT1 knockdown or knockout increases GPR133 signaling, while its overexpression has the opposite effect, without altering GPR133 levels in the plasma membrane. The GPR133-ESYT1 interaction requires the Ca2+-sensing C2C domain of ESYT1. Thapsigargin-mediated increases in cytosolic Ca2+ relieve signaling-suppressive effects of ESYT1 by promoting ESYT1-GPR133 dissociation. ESYT1 knockdown or knockout in GBM slows tumor growth, suggesting tumorigenic functions of ESYT1. Our findings demonstrate a mechanism for the modulation of GPR133 signaling by increased cytosolic Ca2+, which reduces the signaling-suppressive interaction between GPR133 and ESYT1 to raise cAMP levels.